Soviet Diplomacy and Intelligence Efforts to Facilitate Finland’s Withdrawal from the 1941– 1944 War: Insights from Russian Archive - V. S. Khristoforov (Vestnik MGIMO-Universiteta)
Through both intelligence channels and foreign policy efforts, Moscow gathered information in early 1941 about the growing alliance between Berlin and Helsinki, including increased German-Finnish military collaboration, the deployment of German troops and military equipment in Finland, the recruitment of Finnish volunteers for SS units in Germany, the construction of fortifications along the Soviet border, and the massing of Finnish forces near the Soviet frontier. Despite initially maintaining neutrality after Germany's invasion of the USSR, Finland declared war on the Soviet Union on June 26, 1941. The initial phase of the Soviet-Finnish front from July to December 1941 saw military successes favoring Finland. Subsequently, from late December 1941 until summer 1944, a "positional war" ensued with little change to the front line. During this period, Stockholm emerged as a key geopolitical hub where Soviet diplomats, led by A. Kollontai, and intelligence officers navigated the complex task of encouraging Finland to engage in peace talks with the Soviet Union and withdraw from the war. Sweden's neutrality in the conflict and its traditionally strong ties with Finland positioned it as an effective mediator in these negotiations. Additionally, Moscow successfully lobbied Washington to apply diplomatic pressure on Helsinki to initiate negotiations, which gradually began to yield positive results. The multifaceted efforts of Soviet diplomats and intelligence, coupled with A. Kollontai’s active involvement in this diplomatic endeavor, facilitated two rounds of Soviet-Finnish negotiations in Moscow in March and September 1944. While the March talks faltered due to Finnish delegates and political stances, the September negotiations succeeded in persuading Finland to agree to a truce, ceasing hostilities. This diplomatic victory contributed to the gradual disintegration of the anti-USSR coalition led by Germany, with Finland becoming a crucial component to exit this alliance.